Accounting Of Barapan Kebo: "Determining The Price Of Sales" (Empirical Study In Sumbawa Besar District, West Nusa Tenggara) - Kadek Narayana; Ari Surya Dharmawan (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This research is carried out with the aim to know how the process of determining the price of sale of Buffalo on Barapan Kebo customary in Sumbawa Besar regency. The research method on this study uses qualitative methods with the presentation of data based on theoretical frameworks that have been compiled previously. The results of this research show that: the price determination of the sale of buffalo on the customary activities of Barapan Kebo is determined by several criteria that are trusted by the community in Sumbawa Besar District namely: (1) The speed of the buffalo in running and how often the buffalo won the race, (2) with attention to the number and location of the Unyang-unyang(Whirlpool) on the buffalo as a marker of the power of the Buffalo in a run (3) by paying attention to the color from the tail end of the buffalo as a marker of Buffalo stability, (4) and the belief of Buffalo at a high price will give a good saplings to follow the activities of the Barapan Kebo.